Valuing or devaluing nuclear weapons in the war journalism: a cross-national comparative content analysis of news coverage during the Russian war in Ukraine - Yu Guo; Xiubin Duan; Xiaodong Yang (Humanities & Social Sciences Communications)
Abstract This study adopted a comparative content analysis approach to examine the extent of media coverage of the Russian war in Ukraine by three newspapers from the United States, the United Kingdom, and China. Drawing upon the framework of war/peace journalism and valuing/devaluing nuclear weapons frames, this study aimed to compare how the newspapers of the three countries have applied different media frames in their coverage of this military conflict. From February 2022 to January 2023, a total of 2868 newspaper articles from the United States (The New York Times, 1619 articles), the United Kingdom (The Guardian, 1073 articles), and China (Global Times, 176 articles) were selected for quantitative content analysis. Results suggested that The New York Times and Global Times portrayed the war more with the war journalism frame, whereas The Guardian presented a stronger peace journalism frame. Regarding the coverage of nuclear weapons, the three newspapers emphasized the values of nuclear weapons with a neutral tone, and they did not associate nuclear weapons values with a predetermined frame. Furthermore, to understand the dynamic relationship between the evolution of war events and changes in media coverage frames, we examined the changes of frames in three newspapers during the four stages of the war development (1. Outbreak; 2. Pushforward; 3. Counteroffensive; 4. Standoff). Results suggested that as the war progressed, The New York Times significantly reduced its coverage of war news and nuclear weapons news, and began to favor a passive tone towards those involving nuclear weapons. When the war reached a stalemate, The Guardian began to significantly increase its coverage of peace journalism frames. At four stages of the war, China’s Global Times remained neutral, with no significant change in its reporting framework.